Hubungan Antara Pemahaman Hak dan Kewajiban Serta Pemahaman Prosedur Pelayanan Kesehatan Peserta Jamkesmas dengan Pemanfaatan Pelayanan Kesehatan Jamkesmas Di Puskesmas Sedayu I Kabupaten Bantul - Febrianto, Adigama Priamas; Sutisna, Endang; Sumardiyono, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Jamkesmas is a health care insurance program for the poor and unwealthy using social health insurance principal. The purpose is increasing the access and the quantity of health care toward whole of the poor and unwealthy in order to achieve optimal level of public health effectively and efficiently. Preliminary research indicates there is a Correlation between The understanding of Jamkesmas with the use of Jamkesmas Program. The understanding of Jamkesmas is holding potensial role in influencing health care seeking behavior of Jamkesmas participants. Lack of the understanding on rights and obligations, and procedures as Jamkesmas participants in terms of health care impedes health care seeking behavior in Puskesmas (health centers) and hospitals. This study aims to identify and analyze the Correlation between Jamkesmas participants understanding of rights and obligations and service procedures with the level of utilization of Jamkesmas health care at Puskesmas Sedayu I Bantul regency. Methods: This research is an observational analytic research by cross-sectional approach. A total of 100 subjects were selected by purposivesampling is a participant Jamkesmas who check-up their health in Puskesmas Sedayu I Bantul Regency who met the inclusion criteria. Data were collected by direct interview using a questionnaire to patients. That research data were analyzed using Chi Square and processed with the Statistical Product and Service Solutions (SPSS) 21:00 for Windows. Results: There is a statistically significant Correlation between the understanding of rights and obligations of Jamkesmas with Jamkesmas Health Care Utilization and there is no significant Correlation between the Understanding of Jamkesmas Health Care Procedure with Jamkesmas Health Care Utilization Conclusions:There is a statistically significant Correlation between the understanding of rights and obligations of Jamkesmas with Jamkesmas Health Care Utilization and there is no significant Correlation between the Understanding of Jamkesmas Health Care Procedure with Jamkesmas Health Care Utilization. Keywords:Jamkesmas, Understanding, Rights and Obligations, Care Procedure Â